2015
DOI: 10.1109/tia.2015.2453257
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Nonintrusive Efficiency Estimation Technique for Induction Machines Compared to the IEEE 112B and IEC 34-2-1 Standards

Abstract: International efficiency testing standards such as the IEEE 112-B and IEC 34-2-1 can determine an induction machine's efficiency accurately at the cost of hindering the machine's productivity. Alternatively, various methods used to determine a machine's efficiency in-situ do so at the cost of accuracy. This paper proposes a method that determines an induction machine's efficiency over a range of load conditions from tests conducted and centered around one thermally stable load point in the least intrusive mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…T load,Est = I load I rated (T rated − T ambien ) + T ambien (1) where I rated is the rated load current stated on the machine's nameplate, I load is the actual load current, T load,Est is the actual temperature, T ambien is the ambient temperature, and T rated is the rated load temperature…”
Section: Torque and Speed Determination Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T load,Est = I load I rated (T rated − T ambien ) + T ambien (1) where I rated is the rated load current stated on the machine's nameplate, I load is the actual load current, T load,Est is the actual temperature, T ambien is the ambient temperature, and T rated is the rated load temperature…”
Section: Torque and Speed Determination Methodsmentioning
confidence: 99%
“…While effort is being made to design and manufacture more efficient induction motors (IMs), monitoring a machine's operational efficiency helps reduce energy costs by ensuring that it is running in its optimal efficiency range. Numerous works have been published for estimating the efficiency of the electrical machines in situ, under the loaded condition without disturbing their operation [1,2]. To assess energy efficiency and enhance the overall performance of the industrial processes, it is essential to identify energy loss and monitor the efficiency in real time [3].…”
Section: Introductionmentioning
confidence: 99%
“…The authors obtained similar results in Reference [23], where the difference between the measured and estimated efficiency was 0.4% for a 3 kW rated power. In Reference [27], for an 11-kW rated power induction motor, the Realistic Error Estimation (REE) was ±0.24%, which was lower than the Worst Case Estimation (WCE) of the method recommended by the IEEE 112-B standard for polyphase induction motors. In Reference [28], the accuracy difference for a 3-hp machine, when comparing the measured and estimated efficiencies, was 1.2%.…”
Section: Introductionmentioning
confidence: 95%
“…The increasing demand for the use of small AC motors has stimulated research related to the development and enhancement of techniques for the measurement of the motors' efficiency, and for the computation of the associated accuracy [18][19][20][21][22][23][24][25][26][27][28], where we provide a short review of the related research papers. In Reference [9], a comparative analysis of direct and indirect efficiency estimation techniques was presented for a 3 kW, three-phase induction motor, and it was concluded that the direct determination of efficiency should be used for all sizes of induction motors.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the iron loss and copper loss of the motor are calculated, and the relationship between the power loss of the motor and its equivalent circuit parameters is obtained. To reduce interference in the operation, the efficiency change of an induction motor under different load levels is studied in the form of an equivalent circuit in paper [27]. Here, the calculation accuracy is exemplary.…”
Section: Introductionmentioning
confidence: 99%